Peningkatan Keterampilan Non Lokomotor Berbasis Kearifan Lokal Anak Usia 5-6 Tahun - Ulil Inaya; Andi Rezky Nurhidaya; Erwin Nurdiansyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
The purpose of this study was to determine the application of traditional jump rope games and increase gross motor skills at the age of 5-6 years at Aisyiyah Bustanul Athfal Mariso Branch Kindergarten. This research is a Classroom Action Research, the model used is the Kemmis and Taggart model which consists of 2 cycles. The subjects of this study consisted of 12 children, 5 boys and 7 girls. Data collection was carried out by means of observation and documentation. Data analysis techniques used qualitative data analysis and quantitative data analysis. Based on the results of the analysis in cycle I and cycle II, the researcher can conclude that the results of the application of the game can be started with singing, warm-up movements, preparation of places and tools, instructions and examples from the teacher and giving rewards to encourage children's enthusiasm. The physical component of children's gross motor skills has improved well. Based on the gross motor abilities of children in group B can be improved. The gross motor ability of children in cycle I is evidenced by the average category of children's achievement developing as expected while in Cycle II it is in the category of developing very well in training flexibility, balance and agility. Thus, the application of traditional jump rope games can improve gross motor skills of children aged 5-6 years at Aisyiyah Bustanul Athfal Mariso Branch Kindergarten.